Changing local governance, changing citizens - Richardson, Liz; Greasley, Stephen, 1973-; Durose, Catherine (Book collections on Project MUSE., 2009)
This work explains what debates about local governance mean for local people. The book explores governance and citizenship in relation to multiculturalism, economic migration, housing markets, neighbourhoods, and e-democracy in order to establish a contemporary view of the ways that citizens are constituted at the local level.